Czytając Korczaka (Zarys projektu badania dydaktycznego) - Aleksander Połonnikow; Natalia Korczałowa (Problemy Wczesnej Edukacji)
The paper presents a number of problem research situations of reading in the University pedagogical training. The paper’s focus is on the Belarusian State Pedagogical University students’ addressing the heritage of the Polish pedagogue Janusz Korczak. Described are common readers’ strategies used by students in the process of learning and marginal textual tactics creating the possibilities of diversification of readers’ practices in class. The condition for such kind of transformation is Korczak’s specific design of pedagogical statement which enables him to act as a “screen” for students to project and implement their pedagogical experiences.